1998
DOI: 10.3109/10611869808997881
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Fusion Proteins Containing Transferrin and Nerve Growth Factor

Abstract: To explore the ability to use genetic fusions of transferrin as a carrier for brain targeting and delivery, a series of fusion proteins containing both human nerve growth factor (NGF) and human transferrin was produced in mammalian cells. A protein in which the hinge region from human IgG3 joined the carboxyl terminus of NGF and the amino terminus of transferrin formed a covalent homodimer, bound human transferrin receptor, and retained full NGF in PC12 cells. In contrast, proteins in which polypeptide dimeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Others have also found that the insertion of IgG hinge region as a flexible linker between Tf and nerve growth factor (NGF) domains was ineffective for the expression of this fusion protein (12). To further demonstrate the requirement of the helical structure of the linker peptide for the increase of the fusion protein expression, we reversed the DNA sequence coding for the helical peptide to produce a linker with an identical peptide length, but a non-helical structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have also found that the insertion of IgG hinge region as a flexible linker between Tf and nerve growth factor (NGF) domains was ineffective for the expression of this fusion protein (12). To further demonstrate the requirement of the helical structure of the linker peptide for the increase of the fusion protein expression, we reversed the DNA sequence coding for the helical peptide to produce a linker with an identical peptide length, but a non-helical structure.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of a peptide linker with the ability to maintain domain function of the fusion protein is becoming important (912). Recently, we designed a helical linker with 50 amino acids using an EAAAK helix-forming motif based on a previous study (10), and inserted the linker between granulocyte colony stimulating factor (G-CSF) and Tf moieties, leading to increased biological activity (13).…”
Section: Introductionmentioning
confidence: 99%
“…220 By designing conjugates between OX26 and therapeutic agents, such as low molecular drugs (methotrexate), neuropeptides (vasoactive intestinal peptide), polyamide nucleic acids, proteins (never growth factor NGF), which can be transcytosed via the transferrin receptor to the brain side of the blood-brain barrier, the effective concentration of drugs delivered to the brain has been markedly increased compared to the intravenous administration of the drugs alone. [221][222][223][224][225][226] In addition to the chemical conjugation, attempts have also been made to couple the therapeutics to the OX26 antibody using the avidin/biotin systems to promote coupling of biotin and biotinylated drugs to brain transport vectors. [227][228][229] A novel Ab-avidin fusion protein (Ab genetically fused to avidin) was constructed to deliver biotinylated compounds across the blood-brain barrier, and the fusion protein exhibited superior [ 3 H]biotin uptake into brain parenchyma in comparison with the chemical conjugate OX26-SA (Ab chemically conjugated to streptividin).…”
Section: Transferrin Receptors In Drug and Gene Delivery To The Brainmentioning
confidence: 99%
“…Fusion proteins have found applications in a wide spectrum of areas such as the biomedical field [including immunology, cancer research, and drug delivery (17)(18)(19)(20)] and materials science [self-assembled materials (e.g., gels), quantum dot bioconjugates, sensors, and inorganic materials synthesis (21)(22)(23)(24)(25)(26)(27)]. Here we describe new silica-based nanocomposites formed from bioengineered fusion proteins that consist of two components (Fig.…”
mentioning
confidence: 99%